(untitled) (Raparin Journal of Humanities (RJH), 2021)
This research aims to know the impact of investments on the development of the industrial sector in the Kurdistan region of Iraq. In order to achieve the research aim, the reality of investments and the extent of the contribution on the impact of existing investments in the industrial sector have analyzed. The research presented the possible ways, mechanisms, and procedures to develop the industrial sector. The research adopted a descriptive and analytical approach to answer the research questions and determine the impact of investments on the industrial sector. It reached a set of conclusions, the most important of which are: The industrial sector in the Kurdistan region is one of the most important economic sectors because it enjoys appropriate economic resources which assist the sector to develop and grow, where the governorate of Sulaymaniyah is considered as the first rank in terms of the size of invested capital for establishing industrial plants. Finally, the research suggested a number of recommendations, the most important of which are: Rationalizing tax incentives to attract more investments by focusing on directing investments towards productive projects, especially export projects As well as working to use the resources in the region that have not been used so far because there are no industrial companies in this field, in order to diversify industrial products.